2017
DOI: 10.1007/s00701-017-3264-3
|View full text |Cite
|
Sign up to set email alerts
|

Intra-catheter endoscopy for various shunting procedures—a retrospective analysis on surgical practicability, catheter placement, and failure rates

Abstract: Versatile application possibilities of the intra-catheter endoscope reflect the advantages of the technique. Independent of the performed procedure, unintended positionings or even complete catheter misplacements could be avoided. However, in more than one-third of all cases, suboptimal catheter placements became obvious. Interestingly, negative influences on later shunt failures were not seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The complication rate due to VC placement was 13.2%. CSF or delayed shunt infections were determined in 7 patients and a wound-healing disorder in one patient [3]. In our study, we had better catheter placement rate using SG technique (90%) and comparable complication and revision rates.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The complication rate due to VC placement was 13.2%. CSF or delayed shunt infections were determined in 7 patients and a wound-healing disorder in one patient [3]. In our study, we had better catheter placement rate using SG technique (90%) and comparable complication and revision rates.…”
Section: Discussionmentioning
confidence: 53%
“…Several studies reported good success rates, especially with di cult ventricular con gurations. [2,3,5,20,25]. However, these studies did not include a control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows the tip of the VC to be placed in the cerebrospinal fluid (CSF) system under visual control while avoiding touching the ventricular wall or the plexus. In addition, many authors recommend the use of a narrow or wide endoscope tube in difficult ventricular anatomy, where other methods cannot achieve an optimal position [20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%